Taxonomic reassessment and nomenclatural status of Niceforonia dolops and Hylodes philippi (Amphibia: Anura: Strabomantidae) - Sánchez-Vialas, Alberto; Miñarro, Marta; Padial, José M.; Riva, Ignacio De La (Zootaxa, 2023)
The taxonomic and nomenclatural status of Hylodes philippi and H. verrucosus have been in state of flux. Some problems regarding their identity were noticed in 1971, which were partly solved with the finding of the purportedly lost type of H. verrucosus in 2006 and the morphological revisions of both H. philippi and H. verrucous in 2008 and 2012, upon which they were considered conspecific and closely related to the Eleutherodactylus dolops group; H. verrucosus became a junior synonym of H. philippi, and the latter, a nomen dubium within Hypodactylus (later, Niceforonia). The reexamination of the type series of Eleutherodactylus dolops Lynch & Duellman, 1980 and the types of Hylodes verrucosus Jiménez de la Espada, 1875 and H. philippi Jiménez de la Espada, 1875, suggests that they are conspecific. Accordingly, Eleutherodactylus dolops is herein regarded as junior synonym of H. philippi and a new combination, Niceforonia philippi (Jiménez de la Espada, 1875), and a new diagnosis are granted. This species is known from a few scattered localities along the montane forest of the Amazonian versant of the Andes from Orellana and Napo provinces in northern Ecuador to Sibundoy in southwestern Colombia, and little to nothing is known about its natural history and population trends.